Improving functionality of chocolate: A review on probiotic, prebiotic, and/or synbiotic characteristics - Konar, Nevzat; Toker, Omer Said; Oba, Sirin; Sagdic, Osman (ELSEVIER SCIENCE LONDON, 2016)
Background: Chocolate is consumed by people of all ages in all segments of society throughout the world. The popularity of this food is mainly associated with its potential to arouse sensory pleasure and positive emotions. Increasing awareness of the link between healthy eating and well-being is reflected in the current views of the general consumers. Consumers perceive functional foods as a member of the specific food category to which they belong. Also, in developed economies, a key trend at the moment is confectionery products that deliver functional benefits for health and well-being, such as functional chocolate. Scope and approach: In this review, studies related with production of prebiotic, probiotic and synbiotic chocolates as a functional food were investigated and positive and negative aspects of these functional products when compared with standard one were stated, which could shape the following related studies in food area and the production of prebiotic, probiotic and synbiotic chocolates in the food industry. Key findings and conclusions: When the studies related with this topic were investigated it could be concluded that the studies associated with chocolate which could play a role in transportation of probiotics and prebiotics might be supported by studies in which bioavailability and bioaccessibility characteristics of them in vivo and in vitro media will be determined. Moreover, in order to improve bioavailability and bioaccessibility properties product quality optimization studies might be required in the future. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Functional chocolate; Prebiotic; Probiotic; Synbiotic; LACTIC-ACID BACTERIA; MILK CHOCOLATE; SENSORY PROPERTIES; LACTOBACILLUS-RHAMNOSUS; QUALITY CHARACTERISTICS; RHEOLOGICAL PROPERTIES; BULKING AGENTS; INULIN; HEALTH; COCOA; Food Science & Technology